Efeitos protetores do treinamento físico resistido na toxicidade induzida pela doxorrubicina - Feitosa, Larissa Andrade de Sá (2019)
The chemotherapeutic drug doxorubicin (DOX) is used for the treatment of different tumor types, but causes harm to striated skeletal and cardiac muscles. Interventions that may be helpful to the heart and skeletal muscle could have a positive impact on DOX dysfunctions. Resistance training (RT) has demonstrated benefits, such as an increase in muscle strength, muscle hypertrophy and improvements in cardiac autonomic modulation, heart remodeling and hemodynamics, in other physiopathological conditions and may be a beneficial therapy regarding DOX-induced toxicity. The aim of the present study was to evaluate the effects of eight weeks of RT on DOX-induced toxicity to the cardiovascular and musculoskeletal systems. Forty-four male Wistar rats were distributed among three groups: sedentary control (CON), sedentary DOX (DOX) and DOX+RT (DOX + active training). RT was performed 3x/week at 40% of one maximum repetition in the animals treated with DOX (2.5 mg/kg once a week for six weeks). Evaluations were performed on the cross-sectional area of cardiomyocytes (CSAC) and the plantaris muscle (CSAP), muscle strength, hemodynamics, baroreflex spontaneous sensitivity (BRS) and effectiveness index (BEI), vascular autonomic modulation, cardiac autonomic tone, ex vivo ventricular pressure, protein content of phosphorylated Akt and total Akt of the left ventricle and markers of oxidative stress (lipid peroxidation, superoxide generation, the content of sulfhydryl groups, catalase activity and superoxide dismutase activity) of the left ventricle and plantaris muscle. The comparison of the groups was performed using one-way ANOVA followed by Tukey's post hoc test, Kruskal-Wallis test followed by Dunn’s teste and two-way ANOVA followed by Tukey's post hoc test. In the animals treated with DOX, RT led to reductions in diastolic blood pressure, heart rate and sympathetic tone as well as an increases vagal tone, BRS, BEI and vascular autonomic modulation. RT promoted an increase in Akt phosphorylation that led to increase in the CSAC and the development of left ventricular pressure through the increase in myocardial contraction velocity. Regarding markers of oxidative stress, RT led to increases in catalase activity and decreases in generation of superoxide and lipid peroxidation in the heart. RT led to increases in muscle strength in the hind paws, CSAP as well as catalase and superoxide dismutase activity in the plantaris muscle and reductions in the generation of superoxide and lipid peroxidation. The findings demonstrate that RT improve in cardiovascular system BRS and BEI that led to better autonomic control, vascular autonomic modulation and hemodynamic. Exercise improved cardiac contraction and CSAC, as well as increased Akt phosphorylation and decreased oxidative stress. In skeletal muscle we observed attenuation in the reduction of muscle strength, CSAP and oxidative stress. Therefore, resistance training can be employed as a useful strategy for attenuating the adverse effects induced by pharmacological treatment with doxorubicin.